Evaluation of a 2-1-1 Telephone Navigation Program to Increase Cancer Control Behaviors: Results From a Randomized Controlled Trial. Issue 7 (September 2022) - Fernandez, Maria E.; Savas, Lara S.; Atkinson, John S.; Ricks, Katherine Ball; Ibekwe, Lynn N.; Jackson, Inimfon; Castle, Philip E.; Jobe, David; Vernon, Sally W.
Purpose: To evaluate the effectiveness of a telephone navigation intervention for increasing use of cancer control services among underserved 2-1-1 callers. Design: Randomized controlled trial. Setting: 2-1-1 call centers in Houston and Weslaco, Texas (located in the Rio Grande Valley near the Mexican border). Participants: 2-1-1 callers in need of Pap test, mammography, colorectal cancer screening, smoking cessation counseling, and/or HPV vaccination for a daughter (n = 1, 554). A majority were low-income and described themselves as Black or Hispanic. Intervention: Participants were randomly assigned to receive either a cancer control referral for the needed service(s) with telephone navigation from a trained cancer control navigator (n = 995) or a referral only (n = 559). Measures: Uptake of each individual service and any needed service. Analysis: Assessed uptake in both groups using bivariate chi-square analyses and multivariable logistic regression analyses, adjusted for sociodemographic covariates. Both per-protocol and intent-to-treat approaches were used. Results: Both interventions increased cancer control behaviors. Referral with navigation intervention resulted in significantly greater completion of any needed service (OR = 1.38; p = .042), Pap test (OR = 1.56; p = .023), and smoking cessation counseling (OR = 2.66; p = .044), than referral-only condition. Other outcomes showed the same trend although the difference was not statistically significant: mammography (OR = 1.53; p = .106); colorectal cancer screening (OR = 1.80; p = .095); and HPV vaccination of a daughter (OR = 1.61; p = .331). Conclusion: Adding cancer control referrals and navigation to an informational service like the 2-1-1 program can increase overall participation in cancer control services.